TERES: Tail event risk expectile based shortfall - Philipp Gschöpf; Wolfgang Karl Härdle; Andrija Mihoci (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2015)
A flexible framework for the analysis of tail events is proposed. The framework contains tail moment measures that allow for Expected Shortfall (ES) estimation. Connecting the implied tail thickness of a family of distributions with the quantile and expectile estimation, a platform for risk assessment is provided. ES and implications for tail events under different distributional scenarios are investigated, particularly we discuss the implications of increased tail risk for mixture distributions. Empirical results from the US, German and UK stock markets, as well as for the selected currencies indicate that ES can be successfully estimated on a daily basis using a one-year time horizon across different risk levels.
Keywords: C13; C16; G20; G28; 330; expected shortfall; expectiles; tail risk; risk management; tail events; tail moments